Theoretical study of the 3H(p, e+e−)4He and 3He(n, e+e−)4He processes and the X17 anomaly. Issue 1 (1st December 2022) - Viviani, M.
Abstract: The unexpected observation of eccess of events in the angular distribution of e − e+ pairs in various nuclear transitions has spurred a large interest, both experimentally and theoretically. This eccess has been interpreted as the possible existence of a new bosonic particle, the so-called X17, of mass around 17 MeV. In the present work, we investigate theoretically the possible effects of the presence of the X17 in the 3 H( p, e + e − ) 4 He and 3 H( n, e + e − ) 4 He reactions. For these processes it is possible to compute accurate ab initio bound- and continuum-states wave functions, so the existence of X17 can be unambigously revealed. Moreover, by exploiting the rich structure of the 4 He spectrum, it is possible to determine its quantum number, as, for example, if it is either a scalar, a pseudoscalar, a vector, or an axial particle.